EFEK CORIANDRI FRUCTUS (KETUMBAR) TERHADAP SLOW WAVE SLEEP (SWS) - Indrawati, Lili; D. Sitorus, Truly (Jurnal Kedokteran YARSI, 2007)
Traditional remedies have been used by Indonesian people for centuries. One of them which is empirically used as hypnotic sedative is coriandri fructus. The objective of this study was to find out whether cariandri fructus could be used as a sleep medicine by measuring the sleep quality induced. In this study, a true experimental design was employed. Applying a purposive sampling method, 11 apparently healthy adult male fulfilling the inclusion criteria were selected. Each subject was induced to sleep three times, 7.5 hours each and observation through overnight polysomnography was carried out following each treatment. Lorazepam, placebo and coriandri fructus was used to induce the first, second and third sleep respectively. Parameters used in this experiments were Latency to Slow Wave Sleep, Total Time in SWS, and the distribution of SWS.  This study showed that Lorazepam tend to suppress the Latency to SWS compare with the control and Coriandri fructus. There was no SWS deprivation in all groups. Lorazepam tend to suppress SWS on the last 2,5 hours of sleep.